2018
DOI: 10.18203/2394-6040.ijcmph20182189
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants of catastrophic health expenditure and socioeconomic horizontal equity in relation to it: a rural community based longitudinal study in West Bengal

Abstract: Background:Equity in health care is defined as equal access to available care for equal need. Out-of-pocket expenditures are the most inequitable means of health care financing. These payments become catastrophic health expenditure (CHE) if it exceeds the household’s ‘Capacity to Pay’. As fairness is one of the fundamental objectives of the health system, identification of the factors responsible for these expenditures is important. Hence this study was conducted to find out the determinants of CHE and to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Paul et al . [ 5 ] reported a much higher (20.7%) proportion of catastrophic health expenditure in a rural area in West Bengal. Prinja et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paul et al . [ 5 ] reported a much higher (20.7%) proportion of catastrophic health expenditure in a rural area in West Bengal. Prinja et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] and Paul et al . [ 5 ] analyzed that low-income quintiles were associated with catastrophic health expenditure. Most studies showed a high share of OOPE in total household expenditure in lower-income quintiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies elsewhere in Africa, 3,[13][14][15][16][17][18] age of the household head, chronic illness, health insurance, household size, place care was sought, household occupation, traditional healer's, elderly household members, wealth status, educational status and visiting private health facilities influence CHE. Likewise, studies in Asia, [19][20][21][22][23][24][25][26][27] chronic illness, health insurance, injuries, old household head, ethnicity, age of the household head, educational status, income quintile, public facility, gender of household head and household size influence the probability of BOGALE And KASSA…”
Section: Introductionmentioning
confidence: 99%
“…ส่ วนนี ้ เป็ นการศึ กษางานวิ จั ยในอดี ตที ่ เกี ่ ยวข้ องกั บการศึ กษาการตั วชี ้ วั ดความเป็ นธรรมใน ระบบบริ การสุ ขภาพ จากการส ารวจส่ วนใหญ่ งานวิ จั ยนิ ยมใช้ ดั ชนี วั ดความเป็ นธรรมด้ านสุ ขภาพ คื อ ดั ชนี คั ควานี (Kakwani's index) (Goodall & Scott, 2008;Yu, Whynes, & Sach, 2008) (Berki, 1986;Russell, 2004;Wagstaff & van Doorslaer, 2005;Wyszewianski, 1986;Xu et al, 2003อ้ างถึ งใน(van Doorslaer et al, 2007 (Li et al, 2012;Piroozi et al, 2016;Somkotra & Lagrada, 2009;K. Xu et al, 2003) แต่ มี บางวรรณกรรมที ่ นั กวิ จั ยจะน าเกณฑ์ ตั ดสิ นมากกว่ าหนึ ่ งเกณฑ์ มาเปรี ยบเที ยบ กั นซึ ่ งเกณฑ์ เหล่ านั ้ นได้ จากการก าหนดเองโดยก าหนดให้ เป็ นสเกล เช่ น 5% 10% 15% 20% ของ รายจ่ ายทั ้ งหมดในครั วเรื อน (Ghosh, 2011;Knaul et al, 2006;van Doorslaer et al, 2007 (Kavosi et al, 2012;Li et al, 2012;Paul et al, 2018;Somkotra & Lagrada, 2009) Noble et al, 2009) (Myint et al, 2018;Shi et al, 2011;Van Minh et al, 2013;Y. Xu et al, 2019a) ส าหรั บการศึ กษาผลกระทบต่ อการกลายเป็ นคนยากจนจากการจ่ ายค่ ารั กษาพยาบาลด้ วย ครั วเรื อนเอง จากการทบทวนวรรณกรรม พบว่ า แนวทางการศึ กษาประเด็ นนี ้ มี 2 แนวทาง ได้ แก่ แนวทางที ่ 1.…”
Section: งานศึ กษาเกี ่ ยวกั บความเป็ นธรรมในระบบบริ การสุ ขภาพunclassified